STUDI TENTANG IMPLEMENTASI NILAI KARAKTER RELIGIUS DI PANTI ASUHAN AS-SHOHWAH KECAMATAN TAMPAN KOTA PEKANBARU - Latifah Muhammad; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research at backgrounds by mark sense fosterling life background that variably at shohwah's Ace Reformatory namely, fakir, hole in the wall, fatherless, piatu, orphan and waif. With that situation needs intensive handle it deep teach fosterling one of it which is with mengimplementasikan assesses religious character that its aim is that that child coming can answer future daring and can function properly if is reinstated to society. So writer takes research title “ Studi About Religious Character Point Implementation at reformatory Ace shohwah City Looker district Pekanbaru ”. Problem formula on observational it is how implementation assess religious character at Reformatory Ace shohwah City Looker district Pekanbaru?. To the effect this research is subject to be know how implementation assess religious character at Reformatory Ace shohwah City Looker district Pekanbaru. Population in observational it is exhaustive sitter and Ace Reformatory fosterling sohwah City Looker district Pekanbaru who gets its all told be 39 person and total sample 38 person. Data collecting instrument which is questionnaire consisting of 58 item questions / statements. Interview consisting of 17 questions. Data analysed by Descriptive kualitatif passes through percentage. Of respondent answer percentage count as a whole acquired adverse answer as much 49,63% one lays in rank 40% 55%. Hypothesis thus that declare for religious character point implementation which is performed with every consideration at sohwah's Ace Reformatory City Looker district Pekanbaru is refused. Base observational Result, therefore gets to be concluded that studi about religious character point implementation at Reformatory Ace sohwah City Looker district Pekanbaru which is adverse.  Key words: Implementation, Assess Religious Character.